The shadow key : a novel in four branches - Stokes-Chapman, Susan, 1985- (Harper Perennial, 2024)
"Dismissed from his post at a prestigious London hospital, Dr. Henry Talbot has little choice but to accept a mysterious offer of employment as a private physician from an inscrutable lord of a rural manor in Wales. Arriving at Plas Helyg, Lord Julian's isolated estate, Henry can't speak the language and finds himself treated with hostile suspicion by superstitious villagers, whose beliefs in myths and magic he's inclined to dismiss. But when he discovers that his predecessor died under peculiar, inexplicable circumstances, his determination to uncover the truth leads him down a path fraught with danger-made all the more perilous by his headstrong, reluctant ally Linette, Lord Julian's niece. Linette has lived a lonely life as Plas Helyg's unconventional mistress: her uncle treats her with disdain, her father is long dead, and her mother, long plagued by strange spells and believed by everyone around her to be deeply unwell, spends most of her time locked away in her rooms. Fiercely self-reliant, Linette refuses to wear women's clothes, has no interest in marriage, and takes an interest in the welfare of the men working in Lord Julian's mines, against his wishes. Linette has always suspected something is not quite right in the village, but it is only through Henry's dogged investigations that the dark truth about those closest to her will come to light-a truth that will bind hers and Henry's destinies together forever in ways neither thought possible"--